IMPLEMENTASI FUZZY LOGIC DALAM MENENTUKAN HARGA PERBAIKAN ALTERNATOR MENGGUNAKAN METODE MAMDANI - Deni, Irwansyah; Handoko, Koko (Computer Science and Industrial Engineering, 2023)
The alternator is the component of the generator that produces electricity. A short circuit in the alternator causes a surge in electric current so that it can cause an explosion of sparks, it is necessary to prevent an electric short circuit so that maintenance is needed to repair the alternator. Problems in making decisions also occur in companies, in transactions that are used by companies that are still done manually, in determining the price of alternator repairs it is still based on estimates and during the price determination process you have to wait for confirmation from the company's leadership so that the process takes longer and the error rate is relatively high. Fuzzy logic mamdani one method that can be used to overcome this problem. This research will get the best price quickly and minimize the error rate in pricing and adapt it to the implementation design in MATLAB. In the process of determining the repair price, several weighted criteria are required as input variables, namely alternator capacity, level of difficulty and warranty period, which will then produce output variables, namely alternator repair prices. This study aims to assist companies in determining the price of alternator repairs.